Impact of a Child Life and Music Therapy Procedural Support Intervention on Parental Perception of Their Child's Distress During Intravenous Placement. Issue 7 (July 2019) - Ortiz, Gabriela S.; O'Connor, Todd; Carey, Jessa; Vella, Adam; Paul, Audrey; Rode, Diane; Weinberg, Alan
Abstract : Objectives: Child life specialists and music therapists have a unique and integral role in providing psychosocial care to pediatric patients and families. These professionals are trained to provide clinical interventions that support coping and adjustment and reduce the risk of psychological trauma related to hospital visits and health care encounters. The researchers devised a multimodal approach using a combined child life and music therapy intervention to address procedure-related distress in patients receiving intravenous (IV) placement in the pediatric emergency department. The aim of this study was to investigate the efficacy of this collaborative intervention by evaluating parental perception of their child's distress. Methods: This study was a prospective analysis investigating the impact of a child life and music therapy intervention on children aged 4 to 11 years old receiving an IV placement in the pediatric emergency department. Efficacy was evaluated by comparing scores between a 4-question pretest and subsequent 4-question posttest that asked the child's parent to evaluate how they anticipated their child would respond to the procedure, and then to evaluate how they perceived their child to have responded after the procedure. Qualitative data were collected in the form of open-ended comments, which were accommodated at the end of the posttest. Data were analyzed by the Cochran-Mantel-Haenszel method for testing repeated ordinal responses and the PROC GENMOD procedure in the SAS system software. Results: A total of 41 participants were enrolled in this study. Results of the statistical analysis revealed significant differences between all pre- and posttest scores ( P < 0.05), and significant likelihood that the patient would improve relative to the 4 questions, as a result of the child life and music therapy intervention. Conclusions: Improvement was demonstrated across all 4 questions, suggesting that the child life and music therapy intervention supported healthy, adaptive coping and helped to minimize distress experienced by patients during IV placement. These results underscore the importance and potential clinical impact of child life psychological preparation and psychotherapy-based music therapy interventions in reducing distress in pediatric patients during common medical procedures.